2022
DOI: 10.3390/ani12030238
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Supplementation with Red Yeast (Sporidiobolus pararoseus) on Productive Performance, Egg Quality, and Duodenal Cell Proliferation of Laying Hens

Abstract: Nowadays, industrial poultry producers are more focused on the safety of their products, especially contaminants from feedstuffs such as mycotoxin and pesticides. The residue from animal production using antibiotic growth promoters (AGPs) may cause some problems with antimicrobial resistance in human and animals. Red yeast (Sporidiobolus pararoseus) has a cell wall consisting of β-glucan and mannan-oligosaccharides and pigments from carotenoids that may be suitable for use as a substitute for AGPs. The objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…These observations suggest that red yeast reduced the adsorption of mycotoxins by the liver in hens fed with MT + RY and the applied mycotoxins could not increase lipid peroxidation due to the adsorbent properties of red yeast during the application period. The red yeast cell wall acts as a biological agent that binds to mycotoxin upon intake of the contaminated feed in the gastrointestinal tract to eliminate its toxic effect on vital organs ( Kanmanee et al, 2022 ; Srinual et al, 2022 ). In addition to the adsorption and antioxidant properties of red yeast, several studies in chicken have verified its beneficial effects in improving animal health and productivity, acting as a prebiotic with high nutritional value ( Tapingkae et al, 2018 ; Kanmanee et al, 2022 ; Srinual et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These observations suggest that red yeast reduced the adsorption of mycotoxins by the liver in hens fed with MT + RY and the applied mycotoxins could not increase lipid peroxidation due to the adsorbent properties of red yeast during the application period. The red yeast cell wall acts as a biological agent that binds to mycotoxin upon intake of the contaminated feed in the gastrointestinal tract to eliminate its toxic effect on vital organs ( Kanmanee et al, 2022 ; Srinual et al, 2022 ). In addition to the adsorption and antioxidant properties of red yeast, several studies in chicken have verified its beneficial effects in improving animal health and productivity, acting as a prebiotic with high nutritional value ( Tapingkae et al, 2018 ; Kanmanee et al, 2022 ; Srinual et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The red yeast cell wall acts as a biological agent that binds to mycotoxin upon intake of the contaminated feed in the gastrointestinal tract to eliminate its toxic effect on vital organs ( Kanmanee et al, 2022 ; Srinual et al, 2022 ). In addition to the adsorption and antioxidant properties of red yeast, several studies in chicken have verified its beneficial effects in improving animal health and productivity, acting as a prebiotic with high nutritional value ( Tapingkae et al, 2018 ; Kanmanee et al, 2022 ; Srinual et al, 2022 ). However, to the best of our knowledge, there are no studies on the effects of red yeast in interaction with multiple mycotoxins supplementation in the chicken diet at molecular and cellular levels in the liver of laying hens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The biological damage that is caused by oxidative stress which is caused by free radicals is harmful at the cellular level, and it has been linked to health issues that affect animal productivity [ 32 , 33 ]. In addition to their high nutritional value, the cell wall’s component of red yeast can function as mycotoxin binders [ 28 , 34 ] and improve the productive performance of chickens [ 26 , 35 , 36 ]. Tapingkae et al [ 37 ] demonstrated that the new strain of red yeast that is capable of binding ZEA, AFB1, OTA, and trichothecenes has been commercially used to adsorb mycotoxin in animal and poultry diets.…”
Section: Introductionmentioning
confidence: 99%